2010
DOI: 10.1136/oem.2009.051797
|View full text |Cite
|
Sign up to set email alerts
|

First return to work following injury: does it reflect a composite or a homogeneous outcome?

Abstract: The study provides evidence that RTW may reflect a composite outcome when it includes different modes of first RTW. The identified predictive factors appear to exert different mechanisms of action depending on the mode of RTW. The findings suggest that the different modes of RTW may need to be considered independently. The results of the study have potentially important implications for research and insurance practice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 27 publications
1
8
0
1
Order By: Relevance
“…Alternatively, we might not have had adequate study power to detect a statistically significant association between OMPSQ scores and return to work after 24 months. Modified work is seen as a way of facilitating sustainable and timely return to work and minimizing the costs associated with the loss of an injured worker [29,30]. In agreement with Clay et al [30], our data shows that prognostic determinants exert different mechanisms of action depending on the mode of return to work (i.e.…”
Section: Discussionsupporting
confidence: 89%
“…Alternatively, we might not have had adequate study power to detect a statistically significant association between OMPSQ scores and return to work after 24 months. Modified work is seen as a way of facilitating sustainable and timely return to work and minimizing the costs associated with the loss of an injured worker [29,30]. In agreement with Clay et al [30], our data shows that prognostic determinants exert different mechanisms of action depending on the mode of return to work (i.e.…”
Section: Discussionsupporting
confidence: 89%
“…Return to work/activities is often eliminated as an outcome measure because it is determined by a multitude of personal, societal, and systematic factors. (2123) However, we included this outcome measurement because health in general is determined by these same factors. We also did not evaluate the pre- vs postoperative improvement in the meta-analysis, because in the majority of studies this outcome was reported as a continuous variable which could not be transformed into a binary variable.…”
Section: Discussionmentioning
confidence: 99%
“…One is that RTW is never a homogeneous outcome composed of the outcomes of the same duties, modified tasks, or modified hours (12). The other problem is that further subgroup analysis (eg, injury parts, injury severity, occupation, etc) in a study with sufficient numbers of subjects in each subgroup could add useful information on the RTW among patients with traumatic limb injuries.…”
Section: Trajectories Predictors Of Rtw After Traumatic Limb Injurymentioning
confidence: 99%